The Metropolitan Military: Homeownership Resistance to Military Family Housing in Southern California, 1979-1990. (September 2017) - Reft, Ryan
Despite its dependence on military investment, large segments of the Sunbelt have always expressed ambivalence toward military housing. From 1941 to 1973, real estate interests served as the primary resistance to the construction of military housing; however, during the 1970s, due to economic changes, tax revolts, New Right fiscal and social policies, and the transformation to the all-volunteer force (AVF), opposition to military housing transferred from real estate interests to homeowners. From 1979 to 1990, the Navy's attempt to construct military family housing in San Diego encountered angry homeowners who resented the tax exempt status of housing and accused military households of overburdening school infrastructure, reducing property values, and spreading social dysfunction. Demographic changes resulting from the AVF yielded more families and greater ethnic and racial diversity, which failed to align with suburban norms and thereby marginalized service households socially and politically.